Lithium-containing slag and method for producing valuable metal

By optimizing the pretreatment and melting process of lithium-ion battery waste, controlling the mass ratio of Al/Li and Si/Li, increasing the Mn content, and controlling the oxygen partial pressure in the melt, the slag in the smelting of lithium-ion battery waste is solved. The problem of difficult control of melting point and generation amount has achieved high concentration of lithium and efficient recovery of valuable metals.

CN119278282APending Publication Date: 2025-01-07SUMITOMO METAL MINING CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380042843.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-26
Filing Date
2023-03-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the dry smelting process of lithium-ion battery waste, it is difficult to effectively control the melting point and production amount of the slag, resulting in insufficient concentration of lithium content and difficulty in improving the purity of the valuable metal.

Method used

By optimizing the pretreatment and melting process of lithium-ion battery waste, the mass ratio of Al/Li and Si/Li is controlled, ensuring that Al/Li < 5 and Si/Li < 0.7, increasing the Mn content to more than 6%, and in melting The oxygen partial pressure in the body is controlled to be above 10-14 atm and below 10-11 atm to produce highly concentrated Li-containing slag.

Benefits of technology

It effectively suppresses the amount of flux added, reduces the amount of slag generation, improves the concentration efficiency of lithium and the purity of valuable metals, and improves the recovery efficiency and cost-effectiveness of lithium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005152590330000121
    Figure BDA0005152590330000121
  • Figure BDA0005152590330000122
    Figure BDA0005152590330000122
  • Figure BDA0005152590330000131
    Figure BDA0005152590330000131
Patent Text Reader

Abstract

Provided is a Li-containing slag obtained by melting a raw material such as a spent lithium ion battery containing Li and Al, said slag being capable of effectively controlling the melting point of the slag to a prescribed temperature or lower while suppressing the addition amount of a flux, and also capable of effectively concentrating Li while suppressing the amount of the slag. The present invention is a Li-containing slag obtained by melting a raw material comprising a waste lithium ion battery containing lithium (Li) and aluminum (Al), the Li-containing slag being characterized in that: the Li-containing slag has the relationships of Al / Li < 5 and silicon (Si) / Li < 0.7 in terms of mass ratio; the Li-containing slag contains 30% by mass or less of Al, 6% by mass or more of Mn, 3% by mass or more and 20% by mass or less of Li, and 0% by mass or more and 7% by mass or less of Si.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing lithium-containing slag and valuable metals. Background Art

[0002] In recent years, lithium-ion batteries have become popular as lightweight and high-power batteries. Well-known lithium-ion batteries have a structure in which a negative electrode material, a positive electrode material, a separator, and an electrolyte are sealed in an outer can.

[0003] For example, in a lithium-ion battery, the outer can is made of metals such as iron (Fe) and aluminum (Al). In addition, the negative electrode material is made of a negative electrode active material (graphite, etc.) fixed to a negative electrode collector (copper foil, etc.). In addition, the positive electrode material is made of a positive electrode active material (lithium nickel oxide, lithium cobalt oxide, etc.) fixed to a positive electrode collector (aluminum foil, etc.). In addition, the separator is made of a porous resin film of polypropylene, etc. In addition, the electrolyte contains an electrolyte such as lithium hexafluorophosphate (LiPF6).

[0004] One of the main uses of lithium-ion batteries is hybrid vehicles or electric vehicles. Therefore, it is foreseeable that as the life cycle of the car, the lithium-ion batteries carried will be discarded in large quantities. In addition, there are also lithium-ion batteries that are discarded as defective products during manufacturing. It is required to reuse such used batteries or defective batteries generated during manufacturing (hereinafter referred to as "waste lithium-ion batteries") as resources.

[0005] As a method of recycling, a dry smelting process using a high-temperature furnace to melt all the waste lithium-ion batteries has been proposed. The dry smelting process is a method of melting the crushed waste lithium-ion batteries and separating and recovering the valuable metals represented by cobalt (Co), nickel (Ni) and copper (Cu) and the metals with low added value represented by iron (Fe) and aluminum (Al) by using the difference in oxygen affinity between them. In this method, the metals with low added value are oxidized as much as possible to become slag, while the oxidation of the valuable metals is suppressed as much as possible and recovered in the form of alloys.

[0006] For example, in Patent Document 1, a technology regarding Li2O-loaded metallurgical slag is disclosed, characterized in that the Li2O-loaded metallurgical slag contains Al2O3, SiO2, CaO and MnO, and has a weight composition of 3%<Li2O<20%, ​​1%<MnO<7%, 38%<Al2O3<65%, CaO<55% and SiO2<45%.

[0007] However, in the Li2O-loaded metallurgical slag disclosed in Patent Document 1, Al2O3 is contained at a content rate greater than 38%, which not only increases the melting point of the slag, but also increases the amount of slag. Therefore, in the process of manufacturing valuable metals from raw materials such as waste lithium-ion batteries, if such Li2O-loaded metallurgical slag is generated, it is necessary to increase the amount of flux added to lower the melting point of the slag. In addition, the amount of flux added increases, thereby increasing the amount of slag generated (slag amount), so the Li content in the slag decreases, and a slag in which Li is fully concentrated cannot be obtained. In addition, the MnO in the Li2O-loaded metallurgical slag is less than 7% by mass, and the Mn in the raw material is distributed to the metal without being included in the slag, becoming an impurity.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent document 1: Japanese Patent Application Publication No. 2019-502826. Summary of the invention

[0011] Problems to be solved by the invention

[0012] The present invention is proposed based on the above-mentioned actual situation, and its purpose is to provide a slag in which the amount of flux added can be suppressed and the slag melting point can be effectively controlled below a specified temperature in the Li-containing slag obtained by melting raw materials such as waste lithium-ion batteries containing Li and Al, and the amount of slag can be suppressed and Li can be effectively concentrated, as well as a method for producing valuable metals including the slag.

[0013] Means for solving problems

[0014] The present inventors have solved the above-mentioned problems and provided the following solutions.

[0015] (1) The first invention of the present invention is a Li-containing slag obtained by melting a raw material containing waste lithium-ion batteries containing lithium (Li) and aluminum (Al), wherein the Li-containing slag has a relationship of Al / Li<5 and silicon (Si) / Li<0.7 in terms of mass ratio, and the Li-containing slag contains Al at a ratio of less than 30 mass%, Mn at a ratio of more than 6 mass%, Li at a ratio of more than 3 mass% and less than 20 mass%, and Si at a ratio of more than 0 mass% and less than 7 mass%.

[0016] (2) A second aspect of the present invention is a Li-containing slag, wherein in the first aspect, the Li-containing slag has a relationship of Si / Li<0.35 in terms of mass ratio.

[0017] (3) The third invention of the present invention is a method for producing valuable metals, which is a method for producing valuable metals from a raw material containing waste lithium-ion batteries containing lithium (Li) and aluminum (Al), wherein the production method comprises: a pretreatment step, which includes removing an outer can composed of Al from the raw material; and a melting step, which melts the raw material obtained through the pretreatment step to obtain Li-containing slag and a metal containing valuable metals, wherein the Li-containing slag obtained in the melting step has a relationship of Al / Li < 5 and silicon (Si) / Li < 0.7 in terms of mass ratio, and the Li-containing slag contains Al at a ratio of less than 30 mass%, Mn at a ratio of more than 6 mass%, Li at a ratio of more than 3 mass% and less than 20 mass%, and Si at a ratio of more than 0 mass% and less than 7 mass%.

[0018] (4) A fourth invention of the present invention is a method for producing a valuable metal, wherein in the third invention, in the melting step, the oxygen partial pressure in the melt is controlled to be 10 -14 atm and above 10 -11 Below atm.

[0019] Effects of the Invention

[0020] According to the present invention, it is possible to provide a slag capable of suppressing the amount of flux added and effectively controlling the slag melting point to a predetermined temperature or less, suppressing the amount of slag and effectively concentrating Li, and a method for producing a valuable metal including the slag.

[0021] Furthermore, by the melting treatment to generate such Li-containing slag, Mn in the raw material is effectively distributed in the slag, and the purity of metals including valuable metals can be improved. DETAILED DESCRIPTION

[0022] Hereinafter, a specific embodiment of the present invention (hereinafter referred to as "this embodiment") will be described. It should be noted that the present invention is not limited to the following embodiment, and various modifications can be made within the scope of the gist of the present invention.

[0023] 《1. Lithium-containing slag》

[0024] The lithium (Li)-containing slag (hereinafter, also referred to as "slag") of this embodiment is a slag obtained by melting a raw material containing waste lithium-ion batteries containing Li and aluminum (Al). It should be noted that the raw material containing waste lithium-ion batteries refers to a concept including not only used lithium-ion batteries (waste batteries) but also components of the waste batteries.

[0025] The Li-containing slag is used as a raw material for separating and extracting Li and recovering it. Therefore, it is preferable that Li is effectively concentrated in the Li-containing slag and its content ratio is large.

[0026] Specifically, the Li-containing slag of this embodiment is characterized in that the Li-containing slag has a composition of Al / Li<5 and silicon (Si) / Li<0.7 in terms of mass ratio, and the Li-containing slag contains Al at a ratio of less than 30 mass%, Mn at a ratio of more than 6 mass%, Li at a ratio of more than 3 mass% and less than 20 mass%, and Si at a ratio of more than 0 mass% and less than 7 mass%.

[0027] The Li-containing slag contains Al. The Al contained in the Li-containing slag comes from the outer can of the waste lithium-ion battery as a raw material or the collector holding the positive electrode active material. In the Li-containing slag, the Al content is 30% by mass or less. In addition, the Al content is preferably 25% by mass or less, and more preferably 20% by mass or less.

[0028] As described above, by making the Al content ratio 30 mass % or less, the slag melting point can be suppressed, and the amount of flux added at a predetermined ratio relative to Al in the melting process can be suppressed. Furthermore, by suppressing the amount of flux added, the slag amount (slag generation amount) can be suppressed, and the concentration of Li contained in the slag can be increased. That is, Li can be effectively concentrated in the slag.

[0029] In the Li-containing slag, the content of Li is 3% by mass or more. In addition, the content of Li is preferably 4% by mass or more, more preferably 6% by mass or more. In the slag containing 3% by mass or more of Li, Li is effectively concentrated, the melting point of the slag can be reduced, and the cost of recovering Li from the slag can be reduced. It should be noted that the upper limit of the content of Li is not particularly limited, and the upper limit of the content of Li is 20% by mass or less, which can prevent damage to the furnace wall refractory material of the furnace used in the melting process.

[0030] In addition, in the Li-containing slag, the mass ratio of Al to Li, i.e., the value of Al / Li is less than 5 (Al / Li<5). In addition, Al / Li<4 is preferred, and Al / Li<3 is more preferred. As described above, by satisfying the relationship of Al / Li<5, not only the amount of Al2O3 generated in the slag can be reduced, but also the amount of flux added in the melting process can be suppressed, and as a result, the Li concentration in the slag can be effectively increased.

[0031] In the Li-containing slag, Si is contained in a ratio of 0 mass % or more and 7 mass % or less. In addition, the Si content is preferably 5 mass % or less, and more preferably 3 mass % or less. By making the Si content 7 mass % or less, the Li content in the slag can be increased.

[0032] In addition, in the Li-containing slag, the mass ratio of Si to Li, i.e., the value of Si / Li is less than 0.7 (Si / Li<0.7). As described above, by performing a melting treatment to obtain a slag satisfying the relationship of Si / Li<0.7, the Li content in the slag can be effectively increased. That is, in the melting treatment, for example, by adding a flux to suppress the increase in the slag melting point caused by Al2O3 generated in the slag, and by avoiding the use of silicon dioxide (SiO2) or the mixing of Si, which has a lesser effect on lowering the slag melting point, the Li content in the slag can be efficiently increased.

[0033] As a flux, as described later, it is preferable to use calcium oxide (CaO) or the like which has a large effect of lowering the melting point of slag.

[0034] Furthermore, in the Li-containing slag, Si / Li is more preferably less than 0.35 in terms of mass ratio. By satisfying the relationship of Si / Li < 0.35, the Li extraction rate (leaching rate) when separating and extracting Li from the slag can be improved. For example, when Li contained in the Li-containing slag is extracted (leached) into a liquid using an inorganic acid, if SiO is present around Li, its Li extraction rate decreases sharply. Therefore, in the Li-containing slag, Si / Li is preferably less than 0.35, so that Li can be effectively and efficiently separated and extracted.

[0035] In the Li-containing slag, Mn is contained at a ratio of 6% by mass or more. In addition, the content of Mn is preferably 8% by mass or more, and more preferably 9.5% by mass or more. The content of Mn in the Li-containing slag is at least 6% by mass or more, which means that more than half of the Mn contained in the raw material is distributed to the slag. That is, it is a slag that can minimize the distribution of Mn to the metal generated together with the Li-containing slag during the melting process.

[0036] It should be noted that when the Mn content in the Li-containing slag is 6 mass % or more, the Mn content in the metal can be set to 2 mass % or less even when the slag generation amount is the same, and the purity of the valuable metal in the metal can be improved.

[0037] The details will be described later. In the melting process of the raw material containing the waste lithium-ion battery, the Mn content in the Li-containing slag can be set to 6 mass % or more by controlling the oxygen partial pressure in the melt. Specifically, by controlling the oxygen partial pressure of the melt to 10 -14atm and above 10 -11 Atm or less, more than half of the Mn contained in the raw material is distributed to the slag, and distribution of Mn to the metal obtained at the same timing can be suppressed.

[0038] 《2. Method for producing valuable metals》

[0039] The method for producing valuable metals of the present embodiment is a method for separating and recovering valuable metals (e.g., Cu, Ni, and Co) from raw materials of waste lithium-ion batteries containing lithium (Li) and aluminum (Al). Therefore, the method can also be called a method for recovering valuable metals. The method of the present embodiment is mainly based on a dry smelting process, and can also be composed of a dry smelting process and a wet smelting process.

[0040] Specifically, the method of this embodiment comprises: a pretreatment step, which includes removing an outer can composed of Al from a raw material containing waste lithium-ion batteries; and a melting step, which melts the raw material obtained through the pretreatment step to obtain Li-containing slag and metal containing valuable metals.

[0041] Furthermore, in this method, it is characterized in that the Li-containing slag obtained in the melting step has a relationship of Al / Li<5 and silicon (Si) / Li<0.7 in terms of mass ratio, contains Al at a ratio of less than 30 mass%, contains Mn at a ratio of more than 6 mass%, contains Li at a ratio of more than 3 mass% and less than 20 mass%, and contains Si at a ratio of more than 0 mass% and less than 7 mass%.

[0042] As described above, the raw material includes waste lithium-ion batteries. Waste lithium-ion batteries are a concept that includes not only used waste batteries but also components of the waste batteries. In addition, the valuable metal contained in the raw material is not particularly limited as the object of the manufacturing method, for example, at least one metal or alloy selected from the group consisting of copper (Cu), nickel (Ni), cobalt (Co) and combinations thereof.

[0043] [Waste battery pre-treatment process]

[0044] The waste battery pretreatment step S1 is a step of preparing a molten material (molten raw material, furnace charge) for the smelting process when the raw material including the waste lithium-ion battery is melted to obtain a reduction product of Li-containing slag and a metal composed of valuable metals. In particular, the waste battery pretreatment step S1 includes a process of removing an outer can composed of Al.

[0045] Waste lithium-ion batteries are usually a closed system consisting of an outer can made of Al, which contains an electrolyte and active materials of the positive and negative electrodes. Therefore, if they are processed in the original state, there is a risk of explosion, for example, due to the electrolyte inside the outer can. In addition, as mentioned above, since the outer can is mainly made of Al, if the melting process is carried out in the original state, Al is distributed in the slag, and the Al content increases.

[0046] Therefore, in the waste battery pretreatment step S1, at least the treatment of removing the outer can composed of Al is performed. By performing the treatment of removing the outer can, the electrolyte inside the outer can can also be removed, and the treatment of improving safety can be performed. In addition, the recovery productivity of valuable metals such as Cu, Ni, and Co can be improved. In addition, since the mixing of Al from the outer can can be avoided, the Al content ratio in the slag can be reduced. In other words, by removing the outer can in the waste battery pretreatment step S1, the Al content ratio of the slag (Li-containing slag) obtained by the melting treatment can be adjusted.

[0047] As described above, by separating the Al contained in the outer can, the ratio of Al charged in the melting step S3 can be significantly reduced. As a result, the amount of flux used, which is added in proportion to the content of Al, can be significantly reduced. As a result, the amount of slag obtained through the melting step S3 can be significantly reduced, and the concentration of Li contained in the slag can be increased.

[0048] There is no particular limitation on the specific method for removing the outer can. After discharging the waste lithium-ion battery including the outer can, the battery is roasted at a temperature of 200°C to 300°C to remove the electrolyte and obtain the battery contents (roasted product). Furthermore, the obtained battery contents are sieved by pulverizing the obtained battery contents to separate them into the oversize portion containing Al and the furnace charge as the melting object. Even with slight pulverization, Al can easily become a pulverized product, so that Al can be separated efficiently.

[0049] It should be noted that, for the pulverization process, one of the purposes is to improve the reaction efficiency in the dry smelting process after the subsequent process. By improving the reaction efficiency, the recovery rate of valuable metals such as Cu, Ni, and Co can be improved. There is no particular limitation on the pulverization method, and the contents (baked product) of the battery can be pulverized using a conventionally known pulverizer such as a cutting mixer.

[0050] [Preheating process]

[0051] A preheating step S2 can be provided as needed to heat the crushed waste lithium-ion batteries after the waste battery pretreatment step S1 to a predetermined temperature for oxidative roasting. As described above, by performing oxidative roasting in the preheating step S2, impurities contained in the battery contents can be volatilized or thermally decomposed to be removed.

[0052] In the preheating step S2, it is preferred that, for example, the oxidative roasting is performed by heating at a temperature of 700° C. or higher (preheating temperature). By setting the preheating temperature to 700° C. or higher, the removal efficiency of impurities contained in the battery can be improved. On the other hand, the upper limit of the preheating temperature is preferably set to 900° C. or lower, thereby suppressing the thermal energy cost and improving the processing efficiency.

[0053] The oxidative roasting treatment is preferably carried out in the presence of an oxidant. Thus, carbon (C) among the impurities contained in the battery contents can be efficiently oxidized and removed. In addition, Al can be oxidized. In particular, by oxidizing and removing C, the molten particles of the valuable metals locally generated in the subsequent melting step S3 can agglomerate in the absence of physical obstacles caused by C, and the alloy obtained as a melt can be integrated and easily recovered. It should be noted that, generally, due to the difference in affinity between the main elements constituting waste lithium-ion batteries and oxygen, they are easily oxidized in the order of Al>Li>C>Mn>P (phosphorus)>Fe (iron)>Co>Ni>Cu.

[0054] The oxidant is not particularly limited, but preferably uses oxygen-containing gases such as air, pure oxygen, and oxygen-enriched gas from the viewpoint of easy handling. In addition, the amount of the oxidant introduced can be set to about 1.2 times the chemical equivalent required for the oxidation of each substance to be oxidized.

[0055] [Melting process]

[0056] In the melting step (reduction melting step) S3, the crushed material of the waste lithium-ion battery (melted material, furnace loading material) is melted together with a flux (reduction melting) to obtain a reduction product consisting of a molten metal containing valuable metals and a slag containing Li (Li-containing slag). As a result, impurity elements such as Al are contained in the slag as oxides, and P is also included in the slag by being incorporated into the flux. On the other hand, valuable metals such as Cu that are difficult to form oxides are melted and can be recovered from the melt as an integrated alloy.

[0057] Here, in the method of the present embodiment, it is characterized in that the Li-containing slag obtained by the treatment in the melting step S3 has the following composition. That is, the Li-containing slag has a relationship of Al / Li<5 and silicon (Si) / Li<0.7 in terms of mass ratio, and the Li-containing slag contains Al at a ratio of 30 mass% or less, Mn at a ratio of 6 mass% or more, Li at a ratio of 3 mass% or more and 20 mass% or less, and Si at a ratio of 0 mass% or more and 7 mass% or less.

[0058] In the melting process to obtain such Li-containing slag, the amount of flux added can be suppressed and the slag melting point can be appropriately controlled below a predetermined temperature. In addition, since the amount of flux added can be suppressed, the amount of slag generated can be suppressed, thereby obtaining a slag that effectively concentrates Li.

[0059] The Li-containing slag obtained by the melting treatment can be used as a raw material for separating and extracting Li. Therefore, it is preferable that the amount of slag generated by the melting treatment is small, thereby increasing the Li content ratio and becoming a slag in which Li is concentrated.

[0060] It should be noted that the Li-containing slag having the above composition is as described above, and therefore a detailed description thereof will be omitted here.

[0061] In addition, during the melting process, the oxygen partial pressure in the melt generated by melting the raw materials is controlled to be 10 -14 atm and above 10 -11 The oxygen partial pressure in the melt is an index of the reduction degree in the melting process. By controlling the reduction degree so that the oxygen partial pressure is in the above range, it is possible to maintain a high recovery rate of valuable metals, especially Co, and suppress the distribution of Mn as an impurity into the metal. In other words, Mn in the raw material can be efficiently distributed into the slag, and Mn in the metal can be reduced. As a result, valuable metals such as Cu, Ni, and Co can be efficiently distributed into the metal and recovered.

[0062] The oxygen partial pressure in the melt is continuously measured for monitoring, thereby controlling the reduction degree based on the oxygen partial pressure in the melt. For example, if the oxygen partial pressure is greater than 10 -11 atm, then the reduction degree can be increased by adding a reducing agent. -14 atm, it is controlled by adding oxidants to reduce the degree of reduction.

[0063] The method for measuring the oxygen partial pressure is not particularly limited as long as it is a method that can directly measure the oxygen partial pressure in the melt. For example, a method of measuring by inserting an oxygen analyzer equipped with an oxygen sensor (oxygen probe) in a manner that the front end of the oxygen sensor is immersed in the melt can be cited. It should be noted that as the oxygen sensor, a known sensor such as a zirconium oxide solid electrolytic oxygen sensor (oxygen probe) can be used.

[0064] The method of increasing or decreasing the oxygen partial pressure in the melt, in other words, the method of controlling the degree of reduction using the oxygen partial pressure in the melt as an indicator can be carried out by a known method. For example, as described above, a method of introducing a reducing agent or an oxidizing agent into a raw material for a heating and melting process or a melt formed by its melting can be cited. As a reducing agent, materials with high carbon grade (graphite powder, graphite particles, coal, coke, etc.), carbon monoxide, etc., can be used. It is also possible to use a component with high carbon grade in the raw material for a heating and melting process as a reducing agent. In addition, as an oxidizing agent, an oxidizing gas (air, oxygen, etc.), a material with low carbon grade, etc. can be used. It is also possible to use a component with low carbon grade in the raw material for a heating and melting process as an oxidizing agent.

[0065] In addition, the method for introducing the reducing agent or the oxidizing agent can be carried out by a known method. For example, when the reducing agent or the oxidizing agent is a solid substance, it can be introduced by simply putting it into the raw material or the melt. When the reducing agent or the oxidizing agent is a gaseous substance, it can be introduced by blowing it from an inlet of a spray gun or the like provided in the melting furnace. In addition, the timing of introducing the reducing agent or the oxidizing agent is not particularly limited. For example, the reducing agent or the oxidizing agent can be introduced together when the raw material for the heating and melting process is put into the melting furnace, or the reducing agent or the oxidizing agent can be introduced at the stage where the raw material is melted and becomes a melt.

[0066] Preferably, a reducing agent or an oxidizing agent is introduced into a melting furnace simultaneously with the raw materials to be heated and melted, and the oxygen partial pressure in the melt is measured at the stage when the raw materials are melted to form a melt, and whether to introduce an additional reducing agent or an oxidizing agent is determined based on the measurement result. For example, when the measured value of the oxygen partial pressure deviates from the target value, it is sufficient to introduce an additional reducing agent or an oxidizing agent, while on the other hand, when it is close to the target value, it is not necessary to introduce an additional reducing agent or an oxidizing agent.

[0067] It should be noted that the Co grade in the slag can also be used as an indicator of the reduction degree, and the reduction degree of the melting process can be controlled. The slag is sampled and the Co grade is analyzed. If the obtained Co grade is, for example, less than 0.1% by mass, an oxidant is added to control the reduction degree. If the obtained Co grade is greater than 1% by mass, a reducing agent is added to control the reduction degree. By controlling the reducing agent in this way, Mn in the raw material can also be efficiently distributed to the slag, and Mn in the metal can be reduced. As a result, valuable metals such as Cu, Ni, and Co can be efficiently distributed to the metal and recovered.

[0068] As the flux added in the melting process, it is preferred to include a flux containing an element that forms a basic oxide with a low melting point by incorporating an impurity element. Among them, it is more preferred to include a calcium compound from the viewpoint of being cheap and stable under normal temperature conditions. Specifically, as the calcium compound, for example, calcium oxide and calcium carbonate can be used.

[0069] The heating temperature (melting temperature) in the melt treatment is not particularly limited, but is preferably set to be above 1300°C, and more preferably set to be above 1350°C. By performing the melt treatment at a temperature above 1300°C, valuable metals such as Cu, Ni, and Co are efficiently melted to form an alloy in a state where the fluidity is sufficiently improved. Therefore, the separation efficiency of the valuable metals and impurity components in the slag separation step S4 described later can be improved. It should be noted that when the heating temperature is less than 1300°C, the separation efficiency of the valuable metals and impurities may be insufficient. In addition, as the upper limit of the heating temperature in the melt treatment, it is preferably set to be below 1600°C. When the heating temperature is greater than 1600°C, thermal energy is wasted, the consumption of refractory materials such as crucibles and furnace walls also becomes intense, and productivity may decrease.

[0070] In addition, when heating in the melting process, at the stage of reaching the heating temperature, the fluidity of the melt is low and there is a melting residue, so it is necessary to keep the heating temperature for example for more than 30 minutes. It should be noted that it is preferred that the inside of the crucible is finally observed and an iron measuring rod is used to confirm whether it has completely become a melt. After melting, the metal with high fluidity and the slag are separated into a lower layer of metal and an upper layer of slag in the crucible according to their specific gravity. Then, cooling and pulverization are carried out.

[0071] It should be noted that during the melting process, dust, exhaust gas, etc. may be generated, which can be rendered harmless by performing conventionally known exhaust gas treatment.

[0072] [Slag separation process]

[0073] In the slag separation step S4, slag is separated from the reduction product obtained in the melting step S3 and metals containing valuable metals are recovered. Thus, the metal to be manufactured is obtained. As described above, the metal as the reduction product and the slag are separated in the crucible according to the difference in their specific gravities, so the slag can be separated and the molten metal can be efficiently recovered.

[0074] Furthermore, as described above, the slag separated from the reduction product is a Li-containing slag in which Li is efficiently concentrated, and can be separated and recovered from the reduction product and used as a raw material for separating and extracting Li.

[0075] Example

[0076] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the following examples at all.

[0077] (1) Recovery of valuable metals

[0078] [Examples 1 to 4]

[0079] Valuable metals are recovered using waste lithium-ion batteries as raw materials. The recovery is carried out according to the following process.

[0080] <Waste battery pre-treatment process (preparation process)>

[0081] As waste lithium-ion batteries, 18650 cylindrical batteries, used square batteries for vehicles, and defective batteries recovered in the battery manufacturing process were prepared. These waste batteries were immersed in salt water to discharge, and then the water was removed. They were then calcined at 260°C in the air to remove the electrolyte and obtain the battery contents.

[0082] <Crushing process (preparation process)>

[0083] The obtained battery contents were crushed using a crusher (Good Cutter, manufactured by Ujiie Manufacturing Co., Ltd.) and then sorted using an aluminum separator using eddy current. The crushed material was sieved using a vibrating screen to separate aluminum into an oversize fraction and a undersize fraction as a charge.

[0084] <Oxidation roasting process>

[0085] The obtained pulverized product (charged product) was oxidatively calcined to obtain an oxidatively calcined product. The oxidative calcination was performed in the atmosphere at 900° C. for 180 minutes using a rotary kiln.

[0086] <Reduction melting process>

[0087] Graphite as a reducing agent was added to the obtained oxidized roasted product in an amount of 0.6 times the total molar number of the valuable metals (Cu, Ni, Co), i.e., 1.2 times the molar number required for the reduction of the valuable metals, to obtain a slag composition as shown in the following Table 1. Furthermore, calcium oxide (CaO) was added as a flux so that the Al / Ca ratio of the slag was 0.99 to 2.67 and mixed, and the obtained mixture was charged into an alumina (Al2O3) crucible.

[0088] Then, the mixture loaded into the crucible was heated to perform a reduction melting treatment to alloy the valuable metals and obtain a reduction product containing an alloy and slag (Li-containing slag). The reduction melting treatment was performed by resistance heating at a temperature of 1450°C and a time of 60 minutes. During the reduction melting treatment, an oxygen analyzer with an oxygen probe (OXT-O, manufactured by Kawase Electric Industry Co., Ltd.) at the front end was used to measure the oxygen partial pressure in the melt. In addition, during the reduction melting treatment, the oxygen partial pressure in the melt was controlled to be between 10 -14 atm~10 -11 It should be noted that the oxygen partial pressure is controlled by adding graphite or blowing air with a blowgun.

[0089] <Slag separation process>

[0090] Slag (Li-containing slag) is separated from the obtained reduction product, and the alloy is recovered as the recovered alloy.

[0091] [Comparative Examples 1 and 2]

[0092] In Comparative Example 1, the reduction degree was controlled so that the oxygen partial pressure in the melt was less than 10 -14 Atm, the treatment was carried out in the same manner as in Example 1 except that the above conditions were 0.5% by mass. As a result, the Mn grade in the obtained Li-containing slag was less than 6% by mass.

[0093] In Comparative Example 2, the same treatment as in Example was performed except that Al separation was not performed. As a result, the Al / Li ratio of the obtained Li-containing slag was 5 or more, and the Mn grade was less than 6% by mass. In addition, the Al grade in the raw material was 20% by mass.

[0094] (2) Evaluation

[0095] <Composition analysis of slag>

[0096] The components of the Li-containing slag separated from the reduction product were analyzed as follows: That is, the obtained slag was cooled, pulverized, and chemically analyzed.

[0097] (3) Results

[0098] Tables 1 and 2 below show the compositions of Li-containing slags obtained by the respective treatments of Examples 1 to 4 and Comparative Examples 1 and 2. Table 3 below shows the results of treatment conditions such as the amount of flux added and the amount of slag generated, and the Mn grade in the metal and the Co grade in the slag.

[0099] Table 1

[0100]

[0101] Table 2

[0102]

[0103] Table 3

[0104]

[0105] As shown in the above table, in Comparative Example 2, the amount of flux added / raw material was 0.39, whereas in Examples 1 to 3, the amount of flux added / raw material was 0.08, and in Example 4, the amount of flux added / raw material was 0.16. In addition, in Comparative Example 2, the amount of slag generated / raw material was 0.95, whereas in Examples 1 to 3, the amount of slag generated / raw material was 0.46 to 0.54, and in Example 4, the amount of slag generated / raw material was 0.55.

[0106] That is, it can be seen that by performing treatment to obtain the Li-containing slag of the composition in Examples 1 to 4, the amount of flux added can be reduced, thereby effectively reducing the amount of slag generated. As a result, Li in the Li-containing slag is effectively concentrated, and in Examples 1 to 4, 6 mass % or more of Li can be contained in the slag.

[0107] In addition, the Mn content in the Li-containing slag obtained in Examples 1 to 4 was 6% by mass or more, and more than half of the Mn contained in the raw material was efficiently distributed to the slag. As described above, the reduction degree was controlled so that the oxygen partial pressure was 10 -14 atm and above 10 -11 Atm or less, the distribution of Mn to the metals obtained at the same time can be minimized. Specifically, the Mn grade in the metal can be set to 2 mass % or less.

[0108] It should be noted that, as mentioned above, the oxygen partial pressure in the melt is controlled outside the above range, i.e., less than 10 - 14 Atm, the Mn grade in the obtained Li-containing slag was less than 6 mass %, and the Mn grade in the metal was 2.90 mass %, and a larger proportion was distributed in the metal than in the examples.

Claims

1. A Li-containing slag, which is obtained by melting a raw material containing waste lithium-ion batteries containing lithium Li and aluminum Al, wherein: The Li-containing slag has a mass ratio of Al / Li<5 and Si / Li<0.7, The Li-containing slag contains Al at a ratio of 30 mass % or less, Mn at a ratio of 6 mass % or more, Li at a ratio of 3 mass % or more and 20 mass % or less, and Si at a ratio of 0 mass % or more and 7 mass % or less.

2. The Li-containing slag according to claim 1, wherein The Li-containing slag has a relationship of Si / Li<0.35 in terms of mass ratio.

3. A method for producing valuable metals, which is a method for producing valuable metals from raw materials containing waste lithium ion batteries containing lithium Li and aluminum Al, wherein: The manufacturing method has the following features: A pre-treatment step, the step comprising removing an outer can made of Al from the raw material; as well as a melting step of melting the raw material obtained in the pretreatment step to obtain Li-containing slag and metals containing valuable metals, The Li-containing slag obtained in the melting step has a mass ratio of Al / Li<5 and Si / Li<0.7, The Li-containing slag contains Al at a ratio of 30 mass % or less, Mn at a ratio of 6 mass % or more, Li at a ratio of 3 mass % or more and 20 mass % or less, and Si at a ratio of 0 mass % or more and 7 mass % or less.

4. The method for producing a valuable metal according to claim 3, wherein: In the melting step, the oxygen partial pressure in the melt is controlled to be 10 -14 atm and above 10 -11 Below atm.

Citation Information

Patent Citations

  • Lithium-rich metallurgical slag

    JP2019502826A